Hospital Dentistry in the Intensive Care Unit: A literature review (Research, Society and Development, 2023)
At this moment, one of the great changes in the management of patients with serious diseases is the need for a multidisciplinary team. There is no way to think about complete care if there is no inclusion of professionals in the field of dentistry, for example, since the oral cavity is an integrated and central part of the individual. Therefore, Dentistry has also been adjusting to this new context and, in recent years, it has presented several studies that show the role of dentists, directly or indirectly, in the management of these patients. Studies show that when a complex patient is monitored by a multidisciplinary team, there is not only a significant gain in quality of life, but also an increase in survival, that is, the patient lives longer and better. In this sense, this article sought to carry out a narrative literature review in order to verify the importance of hospital dentistry, emphasizing its role in the care of patients in the ICU. Current dentistry can and should provide safe care for different patients in the hospital area, however, it is reasonable for professionals to be aware of issues such as physical evaluation, medical history, monitoring and possible drug interactions.